Bergenin Attenuates Hepatic Fibrosis by Regulating Autophagy Mediated by the PPAR-γ/TGF-β Pathway - Yujing Xia; Jingjing Li; Kan Chen; Jiao Feng; Chuanyong Guo (PPAR Research)
Liver fibrosis is a pathological process involving diffuse extracellular matrix (ECM) deposition in the liver. It is typical of many chronic liver diseases, including cirrhosis, and effective drugs are needed. In this study, we explored the protective effect of bergenin on liver fibrosis induced by carbon tetrachloride and bile duct ligation. A variety of molecular biological methods (qRT-PCR, western blotting, and immunohistochemistry) were employed to confirm the increased degree of hepatocyte injury and ECM formation in the disease model, consistent with autophagy and activation of the TGF-β pathway. Bergenin activated PPAR-γ and inhibited TGF-β and autophagy and decreased liver fibrosis by inhibiting hepatocyte necrosis and ECM formation in a dose-dependent manner. The results suggest that bergenin may be a promising drug candidate for the treatment of liver fibrosis.